Accurate measurements of plate thickness with variable lift-off using a combined inductive and capacitive sensor. (March 2020) - Salas Avila, Jorge R.; Lu, Mingyang; Huang, Ruochen; Chen, Ziqi; Zhu, Shuang; Yin, Wuliang
Abstract: In eddy current testing, lift-off variations between sensor and sample plate affect sensor inductance and consequently inferred thickness. In this paper, a novel combined inductive and capacitive sensor is designed in which the output of the capacitive sensor can be used to infer the lift-off. An algorithm is proposed to combine the inferred lift-off and the inductance measurement for predicting thickness. The effect of lift-off variations is significantly reduced using this combined sensor approach. Compared to the multi-frequency thickness measurements in our previous work, this only requires a single frequency measurement for each of the capacitive and inductive modalities, leading to a relaxation of the instrument and measurement requirements.